Handlingens logik - Bjerre, Henrik Jøker (Slagmark - Tidsskrift for idéhistorie, 2018)
Alenka Zupančič’ work on Immanuel Kant (Ethics of the Real, 2000) marks her entrance onto the international philosophical scene and places her among the three giants of contemporary Slovenien philosophy. In this article, Zupančič’ investigation of Kantian ethics is presented with a particular focus on the so called ‘logic of the act’, which Zupančič claims has been forgotten or repressed in recent Kant scholarship. By reading Kant with Lacan and showing how any act worthy of the name has a characteristic similar to Lacan’s concept of the drive, Zupančič brings forward a new, much more radical and a bit scary Kant – one that also represents a way of overcoming the moral nihilism of contemporary society.